2014
DOI: 10.1111/all.12528
|View full text |Cite
|
Sign up to set email alerts
|

Google unveils a glimpse of allergic rhinitis in the real world

Abstract: Google Trends (GT) is a Web-based surveillance tool used to explore the searching trends of specific queries on Google. Recent studies have suggested the utility of GT in predicting outbreaks of influenza and other diseases. However, this utility has not been thoroughly evaluated for allergic diseases. Therefore, we investigated the utility of GT for predicting the epidemiology of allergic rhinitis. In the USA, GT for allergic rhinitis showed repetitive seasonality that peaked in late April and early May and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…Recent studies have suggested the utility of GT for assessing the seasonality of allergic diseases [12-17] and for detecting influenza epidemics [18]. GT data may closely reflect the real-world epidemiology of allergic rhinitis (AR) and could potentially be used as a monitoring tool for AR [19]. However, besides the translation of the terms in different languages, cultural differences and different methods of accessing knowledge exist between countries and the same terms are not used similarly in all countries [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested the utility of GT for assessing the seasonality of allergic diseases [12-17] and for detecting influenza epidemics [18]. GT data may closely reflect the real-world epidemiology of allergic rhinitis (AR) and could potentially be used as a monitoring tool for AR [19]. However, besides the translation of the terms in different languages, cultural differences and different methods of accessing knowledge exist between countries and the same terms are not used similarly in all countries [20].…”
Section: Introductionmentioning
confidence: 99%
“…27 Previous studies have also found that allergic rhinitis ( which is related to allergic conjunctivitis), assessed through Google Trends, peaked in the spring, similar to our findings for allergic conjunctivitis. 28 This finding suggests some overlap of allergic conjunctivitis and allergic rhinitis in social media data and clinical diagnoses. 5 We also found differences in allergic vs nonallergic conjunctivitis where EMR data on nonallergic conjunctivitis correlated strongly with Google USA search results for pink eye but not significantly with UCSF diagnoses of allergic conjunctivitis or Google USA search results for eye allergy .…”
Section: Discussionmentioning
confidence: 93%
“…Other studies have investigated allergic rhinitis, which has an ocular component, and have suggested a strong correlation of allergic rhinitis with internet-based Google searches, web traffic logs, and other related terms such as medications . 28 We compare the seasonality of conjunctivitis in online searches in the United States with the seasonality observed in an EMR system from a tertiary care center. We compare that correlation of conjunctivitis-related seasonality with that of other eye-related and of non–eye-related online searches and EMR data as well as with Tweets about pink eye.…”
mentioning
confidence: 99%
“…For example, we exclude metrics based on seasonality [11,130], pollen counts [58,165], over-the-counter drug sales volume [82,98], and emergency department visits [52]. …”
Section: Related Workmentioning
confidence: 99%